(untitled) (CAHIERS MAGELLANES-NS, 2024)
In this article, the scientific aspects of organizing students' independent education, the theoretical and practical bases of their independent work have been developed, and the processes necessary for students' independent work have been researched. The main forms and types of independent learning of students are described in detail, and the methods of independent work that they can perform both in theoretical and practical lesson processes are shown. Methodical recommendations were given in order to attract students to independent work, which in turn is a guide for those engaged in independent education. Key words: independent education, students, creativity, educational technologies, educational process, knowledge, skills, competence, curriculum, educational materials.